Artikulasi Sosiologi Novel dalam Karya Semesta dan Kejutan-NyaSerta yang Dirahasiakan Langit - Anrico Alamsyah (Fakultas Ilmu Sosial dan Ilmu Politik, 2024)
Sociology and literature are two scientific disciplines which, if they support each other and complement each other, will produce works that are very beautiful and provide benefits to humanity. Both are concerned with humans in society and human efforts to adapt and human efforts to bring about good change in society. Human adaptation in the midst of social society which is formed by the influence of sociology and sociologists will be a unique and interesting idea for writers to create imaginatively. This is what ultimately makes sociology and literature have a significant common ground on a problem. The novel, which is the main genre of literature in today's industry, is considered an attempt to recreate the social world, including human relationships with their families, their environment, politics, the state and various social problems. The novel deals with social, economic and political textures which are also matters of sociology. Therefore, the novel 'Semesta dan Kejutan-Nya' and the novel 'Yang Dirahasiakan Langit' try to be a vitamin in society by highlighting several problems, especially those being experienced by young people. Even though it is packed with a romantic storyline, ‘Semesta dan Kejutan-Nya' along with 'Yang Dirahasiakan Langit' contains life values and intersects with social texture. Moreover, 'Semesta dan Kejutan-Nya' and the novel 'Yang Dirahasiakan Langit' appear fresh in the world of Indonesian literature by collaborating with other works in it, namely illustrations/artwork, original music and music videos. It is hoped that the presence of these other works will be able to spark interest in reading among the Indonesian people.
Entry oleh Arif 2026 Maret 25
Keywords: Sociology; literature; novel; ‘Semesta dan Kejutan-Nya'; 'Yang Dirahasiakan Langit’